The Influence of Cow Manure and Super Natural Nutrition Liquid Organic Fertilizer on the Growth and Results of Sweet Corn (Zea mays saccharata Sturt.) Honey Varieties - Gregorius Galu, Hery Sutejo, Legowo K . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
The purpose of this research is to know the effect of organic cow manure of super natural nutrition on the growth and yield of sweet corn plant, and also to know the concentration of liquid organic fertilizer super natural nutrition to get maximum result.Place of study in Farmers Group Sumber Rezeki, Mekar Village Susuk Luar, Sandaran District, East Kutai Regency. The study was conducted in February 2016 until June 2016. The study used factorial analysis 4 x 4 and arranged in Randomized Block Design (RAK), with 3 groups (blocks). The research consisted of 2 factors of treatment, namely: Factor I is Type Cage Manure Cow (P), consist of 4 level, that is: without cow manure or control (p0), dose of fertilizer 2.5 ton / ha equal 1 kg / plot plants (p1), doses of 5 ton / ha equivalent of 2 kg / plot of plant (p2), and fertilizer dose 7.5 ton / ha equal 3 kg / ha (p3). Factor II is the Dosage of Super Natural Nutrition (N) Organic Liquid Fertilizer, consisting of 4 levels, namely: without organic fertilizer SNN liquid or control (n0), concentration 1 ml / l.air (n1), concentration 2 ml / l.air (n2), and a concentration of 3 ml / l.air (n3).The results showed that cow manure was very significant effect on plant height 15 days, age 30 days and age 45 days after planting, length of tuna, cob diameter and cob production per hectare. No significant effect on the age of male and female flowers. The heaviest cob production was found in the treatment of p3 (fertilizer dose 7.5 tons / ha), ie 7.04 tons / ha, the lightest was in the treatment of p0 (control treatment), ie 6.49 tons / ha.The treatment of liquid organic fertilizer SNN has very significant effect on plant height aged 15 days, age 30 days and age 45 days after planting, length of cob, diameter of cob and cob production per hectare. No significant effect on the age of male and female flowers. The heaviest cob production was found in the treatment of n 3 (concentration 3 ml / l.air), ie 6.55 ton / ha, the lightest was in treatment n0 (control treatment), ie 6.49 ton / ha.Treatment interaction had significant effect on plant height 15 days after planting. No significant effect on plant height aged 30 days and age 45 days after planting, age out male and female flowers, length of cob, diameter of cob and cob production per hectare.